Experience of workplace violence during medical speciality training in Turkey - Acik, Yasemin; Deveci, Erhan; Gunes, Gulsen; Gulbayrak, Canan; Dabak, Sennur; Saka, Gunay; Tokdemir, Mehmet (Oxford Univ Press, 2008)
Aims To determine the type, extent and effects of workplace violence among residents during postgraduate speciality training in various departments of medical schools in Turkey. Methods A cross-sectional survey was conducted in seven medical schools representing all geographical regions of Turkey. All physicians in speciality training in the selected medical schools were asked to complete a semi-structured 'violence questionnaire' addressing the type (emotional, physical and sexual) and extent of violence experienced, the perpetrators of the violence and the victim's reactions to the experience. Results A total of 1712 residents out of 2442 completed the questionnaire. In all, 68% indicated they had experienced some form of workplace violence, 67% had experienced verbal violence, 16% had experienced physical violence and 3% had experienced sexual violence. The victims' most prevalent reactions to violence included being deeply disturbed but feeling they had to cope with it for the sake of their career (39%), being distressed (26%) but considering that such events are common in all occupations and discounting it and being confused and bewildered and unsure how to respond (19%). The most frequently named perpetrators of verbal violence were relatives/friends of patients (36%) and academic staff (36%), followed by other residents/senior residents (21%), patients (20%), heads of department (13%) and non-medical hospital staff (6%). Conclusions Physicians in speciality training in medical schools in Turkey are subject to significant verbal, physical or sexual violence. Precautions to prevent such exposure are urgently needed.
Keywords: health care workers; occupation; workplace violence